The Galician Language in the Mirror. The Editing and Analysis of Six Carols Sung Outside Galicia before 1650 - Álvarez, Rosario (Madrygal. Revista de Estudios Gallegos, 2017)
Six carols sung in Galician, although probably produced in Spanish- or Portuguese speaking areas before 1650 (Valladolid, Toledo, Seville, Jerez de la Frontera, Lisbon and Mexico), have been transcribed and studied. They are non-parodic carols in which language is the feature which best identifies the humble children, men and women of Galicia who gather to celebrate the birth of another poor Galician, the boy who is set to become their new lord and redeemer. They are texts which present different degrees of linguistic hybridity, owing to the characteristics of the Galician system at the time, the accommodating of an audience that speaks Spanish or Portuguese, textual transmission or an attempt to hypercharacterise. The objective of this study, in addition to contributing to the knowledge of this selection specifically, is to erase the suspicion of falsification which has been cast unfairly over the entire and broad corpus of carols, without distinctions: the task of philological editing enables the analysis of linguistic hybridization and the separation of imitative characteristics/texts from authentic Galician characteristics/texts, and to establish a relative chronology between variants and their geographical itinerary, as well as to encourage the knowledge of Galician during this period, so in need of new information and new texts. Furthermore, it will be demonstrated how, through the most recurrent phenomena (real or unauthentic), a set of traits that other Hispanic territories would employ to construct the linguistic portrait of Galician speakers can be obtained.